Layered metal-dielectric waveguide: subwavelength guidance, leveraged modulation sensitivity in mode index, and reversed mode ordering - Yan, Min; Thylén, Lars; Qiu, Min (Optics express, 2011)
We describe a layered metal-dielectric waveguide, whose fundamental mode has an effective index as high as 7.35 at 1.55 μm, enabling subwavelength spatial confinement. The loss is found to be reasonable in relation to the confinement. The indefinite dielectric tensor of the stratified metamaterial core generally leads to multimode operation of the waveguide, exhibiting a "reversed" mode ordering contrary to conventional waveguides. The waveguide features a strong leveraging in modal index change subject to a change of index in the dielectric layers, opening the design possibilities of very compact active electro-optic devices.